2008
DOI: 10.1210/en.2007-1503
|View full text |Cite
|
Sign up to set email alerts
|

Identification of KiSS-1 Product Kisspeptin and Steroid-Sensitive Sexually Dimorphic Kisspeptin Neurons in Medaka (Oryzias latipes)

Abstract: Recently, a novel physiologically active peptide, kisspeptin (metastin), has been reported to facilitate sexual maturation and ovulation by directly stimulating GnRH neurons in several mammalian species. Despite its importance in the neuroendocrine regulation of reproduction, kisspeptin neurons have only been studied in mammals, and there has been no report on the kisspeptin or kisspeptin neuronal systems in nonmammalian vertebrates. We used medaka for the initial identification of the KiSS-1 gene and the anat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
172
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 211 publications
(189 citation statements)
references
References 59 publications
16
172
0
1
Order By: Relevance
“…Accumulating evidence has provided insight into the involvement of the kisspeptin system in the regulation of neuronal systems other than those involved in vertebrate reproduction, such as those related to complex behaviors, including sexual motivation and arousal states (Parhar et al 2004, Kanda et al 2008, Tena-Sempere 2010a, Servili et al 2011, Shimizu et al 2012, Zhao & Wayne 2012, Zmora et al 2012, Escobar et al 2013a. Expression levels of kiss and kissr in the brain and, to a lesser extent, in the gonad have been analyzed in several non-mammalian species, including amphibians (Chianese et al 2013) and fish (Mohamed et al 2007, Nocillado et al 2007, Biran et al 2008, Filby et al 2008, van Aerle et al 2008, Kitahashi et al 2009, Mechaly et al 2009, Migaud et al 2012, Alvarado et al 2013, Ohga et al 2013, suggesting a putative role for kisspeptins in controlling reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has provided insight into the involvement of the kisspeptin system in the regulation of neuronal systems other than those involved in vertebrate reproduction, such as those related to complex behaviors, including sexual motivation and arousal states (Parhar et al 2004, Kanda et al 2008, Tena-Sempere 2010a, Servili et al 2011, Shimizu et al 2012, Zhao & Wayne 2012, Zmora et al 2012, Escobar et al 2013a. Expression levels of kiss and kissr in the brain and, to a lesser extent, in the gonad have been analyzed in several non-mammalian species, including amphibians (Chianese et al 2013) and fish (Mohamed et al 2007, Nocillado et al 2007, Biran et al 2008, Filby et al 2008, van Aerle et al 2008, Kitahashi et al 2009, Mechaly et al 2009, Migaud et al 2012, Alvarado et al 2013, Ohga et al 2013, suggesting a putative role for kisspeptins in controlling reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…Gonadal steroid levels seem to be of special importance in case of kisspeptin action on the hypothalamo-pituitary-gonadal axis in fish, since in mammals kisspeptin is responsible for the transmission of the feedback effects of sex steroids on gonadotropin release (Tena-Sempere, 2005;Smith, 2008;Roa, Aguilar, Dieguez, Pinilla, & TenaSempere, 2008;d'Anglemont de Tassigny & Colledge, 2010). Also in fish this can be true, as there are data showing that in the hypothalamus of these vertebrates the cells expressing kisspeptin co-express estrogen receptors, suggesting the role of kisspeptin in the steroid feedback on gonadotropin release (Kanda et al, 2008;Escobar et al, 2010Escobar et al, , 2013Servili et al, 2011;Cowan, Davie, & Migaud, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The interpretation of the results in females was not so straightforward and several causes, as previously discussed, probably contributed to this situation. In medaka, only kiss1 neurons in the nucleus ventralis tuberis (NVT) are positively regulated by ovarian estrogens via their coexpressed erα (Kanda et al, 2008), while estrogen treatment of juvenile zebrafish causes an increase in kiss1 expression, although the effects on kiss2 neurons were much more pronounced (Servili et al, 2011). However, it should be noted that kiss2 expression is up-regulated by E 2 only in the POA of goldfish, showing co-localization with all three types of er genes (Kanda et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Little information regarding kisspeptin gene regulation is available for fish; however, it is known that kiss1 (but not kiss2) neurons are positively regulated by ovarian estrogen at the nucleus ventral tuberis (NVT) in medaka (Oryzias latipes, Temminck and Schlegel) (Kanda et al, 2008;Mitani et al, 2010). Furthermore, kiss2 neurons are sensitive to E 2 in zebrafish (Danio rerio, Hamilton) at the dorsal (Hd) and ventral (Hv) hypothalamus (Servili et al, 2011), and up-regulation of kiss2 neurons by ovarian estrogens was found to occur in the pre-optic area (POA) of goldfish (Carassius auratus, Linnaeus) (Kanda et al, 2012).…”
Section: Introductionmentioning
confidence: 99%